Efektivitas Edukasi Anemia terhadap Peningkatan Pengetahuan Remaja di Desa Kaliwulu, Cirebon - Shafira, Syahla Maitsaa; Islamy, Bellinda Almira Noer; Tanziha, Ikeu; Islamy, Bellinda Almira Noer Islamy (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
Anemia is defined as a condition in which the number of red blood cells or hemoglobin (Hb) levels in the blood are below normal. Anemia in pregnant women can hinder fetal growth and development and can lead to stunting. Adolescent girls are the group most vulnerable to anemia. The purpose of this counseling activity is to increase the understanding of adolescents and the community about the dangers of anemia to reduce anemia cases among adolescents and support efforts to achieve zero stunting in Cirebon Regency, particularly in Kaliwulu Village. This activity was carried out on July 27, 2024, using counseling methods with leaflets and posters as media. The activity began with a pre-test, followed by counseling, and then a post-test. The increase in knowledge was assessed by analyzing the difference between pre-test and post-test scores. The results showed a significant difference between the pre-test and post-test scores (P = 0.003), indicating that anemia education has a positive effect on the respondents' knowledge levels. The authors hope that this activity can continue so that Kaliwulu Village can be free from anemia and achieve zero stunting.